Correction to: Cross-cultural validation of the motivation to change lifestyle and health behaviours for dementia risk reduction scale in the Dutch general population - Tessa Joxhorst; Joyce Vrijsen; Jacobien Niebuur; Nynke Smidt (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.